A Case of Chronic Cutaneous Graft Versus Host Disease with the Clinical Features of Exfoliative Dermatitis - Ahn, Hyo Sang (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
Graft versus host disease (GVHD) has traditionally been divided into acute GVHD and chronic GVHD based on the period it occurs after transplantation. Chronic cutaneous GVHD has traditionally been classified into the lichenoid and scleroderma-like forms. However, unusual clinical forms have been reported such as dermatomyositis, lupus erythematosus and exfoliative dermatitis. A 35-year-old woman presented with a 2 week history of a pruritic maculopapular rash on the whole body. The rash rapidly progressed to confluent erythematous scaly patches and plaques with micaceous scales and this finally led to a generalized exfoliative dermatitis in a 1 month period. Here we present an unusual case of chronic cutaneous GVHD with the clinical features of exfoliative dermatitis. The histopathologic examination demonstrated the lichenoid features of chronic cutaneous GVHD.